Florigen is involved in axillary bud development at multiple stages in Arabidopsis - Niwa, Masaki (Landes Bioscience, 2013)
The wide variety of plant architectures is largely based on diverse and flexible modes of axillary shoot development. In Arabidopsis, floral transition (flowering) stimulates axillary bud development. The mechanism that links flowering and axillary bud development is, however, largely unknown. We recently showed that FLOWERING LOCUS T (FT) protein, which acts as florigen, promotes the phase transition of axillary meristems, whereas BRANCHED1 (BRC1) antagonizes the florigen action in axillary buds. Here, we present evidences for another possible role of florigen in axillary bud development. Ectopic overexpression of FT or another florigen gene TWIN SISTER OF FT (TSF) with LEAFY (LFY) induces ectopic buds at cotyledonary axils, confirming the previous proposal that these genes are involved in formation of axillary buds. Taken together with our previous report that florigen promotes axillary shoot elongation, we propose that florigen regulates axillary bud development at multiple stages to coordinate it with flowering in Arabidopsis.